The Legal Concept of Polygamy Prohibition in Siti Musdah Mulia’s Perspective - Toguan; Arisman (AN NUR: Jurnal Studi Islam, 2023)
Scholars differ in their opinions regarding the status and position of polygamy, but these differences of opinion do not mean that it is haram unless certain conditions are not met. However, one of the figures, namely Siti Musda Mulia, rejects or forbids polygamy absolutely and of course this is very contrary to the understanding of the majority of ulama, both from the fiqh and mufassir circles. For this reason, this research will discuss the legal concept of the prohibition of polygamy according to Siti Musdah Mulia. The aim of this research is to find out the arguments and legal basis used by Musdah Mulia in prohibiting polygamy. This research is qualitative research with the primary source being a book written by Siti Musdah Mulia explaining her argument about the prohibition of polygamy. Apart from that, secondary sources include the results of previous research in the form of scientific journal articles and the opinions of classical scholars in their various leading books (al-kutub al-mu'tabarah). The research results reveal that for Musdah justice in polygamy is a condition that must be fulfilled by polygamists. According to him, polygamy justice must cover all aspects, namely fairness in material and immaterial matters, while the emphasis is on being fair in immaterial matters. Apart from that, the concept of justice in polygamy according to Musdah Mulia is contrary to the opinion of the majority of ulama, which only requires justice in polygamy in material terms.